A Decade Analysis of Curriculum Implementation in Modern Islamic Boarding Schools - Syaharuddin, Syaharuddin; Astuti, Alfira Mulya; Khusniyah, Nurul Lailatul (Universitas Muhammadiyah Mataram, 2024)
The curriculum is one of the keys to the successful implementation of character education in Islamic educational institutions. Therefore, this research aims to systematically and deeply analyze curriculum management in Islamic boarding schools in the modern era. Related research results from Dimension and Scopus databases over the past 10 years are visualized, interpreted, and synthesized systematically. The results show that research on curriculum management in modern boarding schools has been widely studied in various countries in Asia, especially in Islamic-based countries. Further analysis found that modern boarding schools play an important role in shaping character and religious and cultural values that become the foundation for the development of individuals who are noble and integrated in a multicultural society. Furthermore, a curriculum that focuses on the integration between religious education, science, and the role of technology will enrich the learning experience and be able to adapt to the needs of education in the modern era. Despite facing challenges such as the digital divide and limited infrastructure, the transformational approach of pesantren that prioritizes character education and community involvement contributes greatly to sustainable development and relevant education quality. These results can serve as a reference for the development of educational policies that are more responsive to the challenges of the times, as well as provide guidance for Islamic educational institutions in adapting traditional values to the demands of modern society.